ZnCl2 loaded TiO2 nanomaterial: an efficient green catalyst to one-pot solvent-free synthesis of propargylamines. Issue 56 (14th October 2019) - Bankar, Digambar B.; Hawaldar, Ranjit R.; Arbuj, Sudhir S.; Moulavi, Mansur H.; Shinde, Santosh T.; Takle, Shrikant P.; Shinde, Manish D.; Amalnerkar, Dinesh P.; Kanade, Kaluram G.
Abstract : A one-pot green synthesis of propargylamines using nanostructured ZnCl2 –TiO2 under solvent-free conditions has been effectively accomplished. The proposed reaction protocol is sustainable, environment-friendly and offers economic viability. Abstract : One-pot green synthesis of propargylamines using ZnCl2 loaded TiO2 nanomaterial under solvent-free conditions has been effectively accomplished. The aromatic aldehydes, amines, and phenylacetylene were reacted at 100 °C in the presence of the resultant catalyst to form propargylamines. The nanocrystalline TiO2 was initially synthesized by a sol–gel method from titanium(iv ) isopropoxide (TTIP) and further subjected to ZnCl2 loading by a wet impregnation method. X-ray diffraction (XRD) patterns revealed the formation of crystalline anatase phase TiO2 . Field emission scanning electron microscopy (FESEM) showed the formation of agglomerated spheroid shaped particles having a size in the range of 25–45 nm. Transmission electron microscopy (TEM) validates cubical faceted and nanospheroid-like morphological features with clear faceted edges for the pure TiO2 sample. Surface loading of ZnCl2 on spheroid TiO2 nanoparticles is evident in the case of the ZnCl2 loaded TiO2 sample. X-ray photoelectron spectroscopy (XPS) confirmed the presence of Ti 4+ and Zn 2+ species in the ZnCl2 loaded TiO2 catalyst. Energy-dispersive X-ray (EDS) spectroscopy also confirmed the existence of Ti, O, Zn and Cl elements in the nanostructured catalyst. 15% ZnCl2 loaded TiO2 afforded the highest 97% yield for 3-(1-morpholino-3-phenylprop-2-ynyl)phenol, 2-(1-morpholino-3-phenylprop-2-ynyl)phenol and 4-(1, 3-diphenylprop-2-ynyl)morpholine under solvent-free and aerobic conditions. The proposed nanostructure-based heterogeneous catalytic reaction protocol is sustainable, environment-friendly and offers economic viability in terms of recyclability of the catalyst.